One calcium ion may suffice to open the tetrameric cardiac ryanodine receptor in rat ventricular myocytes - Fan, Jing-Song (Blackwell Science Inc, 1999)
1. The release of Ca(2+) from sarcoplasmic reticulum in response to Ca(2+) entering through L-type Ca(2+) channels was studied in isolated voltage clamped rat ventricular myocytes at room temperature using the fluorescent Ca(2+) indicators fluo-3 and Oregon Green 488 Bapta 5N. 2. Depolarizations to positive potentials elicited fluo-3 Ca(2+) transients with rates of rise that were linearly related to the magnitude of the peak measured Ca(2+) current in the presence of Cs(+)-containing pipette solutions. 3. Further experiments utilizing prepulses to preactivate a constant number of channels also revealed a linear relationship between the Ca(2+) transient rate of rise and the magnitude of entering Ca(2+) current at positive potentials. Under these conditions as well, the maximal rates of rise of global myoplasmic Ca(2+) transients were due primarily to Ca(2+) release from the sarcoplasmic reticulum as revealed by effects of ryanodine and caffeine on the Ca(2+) transients. Using such prepulses, linearity between the Ca(2+) transient rate of rise and the magnitude of the peak Ca(2+) current was found under a variety of pulse protocols. 4. Using one such pulse protocol, linearity between the Ca(2+) transient rate of rise and the magnitude of the peak Ca(2+) current was also found when Ca(2+) currents assessed at one potential were reduced in magnitude during the onset of block by application of Co(2+). Using the same pulse protocol, linearity between the Ca(2+) transient rate of rise and the magnitude of the peak Ca(2+) current was also found when use of Cs(+) was avoided by blocking K(+) currents with extracellular TEA and 4-aminopyridine. Linearity in the relationship between the Ca(2+) transient rate of rise and the magnitude of the peak Ca(2+) current was also found when Ca(2+) transients were measured using the low affinity Ca(2+) indicator Oregon Green 488 Bapta 5N in place of fluo-3. 5. These results appear to indicate that the cardiac ryanodine receptor is capable of being activated by only one calcium ion. Alternative interpretations of the data are discussed.